Variations in food habit of the Himalayan mahseer - Tor putitora (Ham.) inhabiting the Ganga river system in Garhwal region - Kishore, B; Bhatt, J P; Rawat, V S; Nautiyal, P (Indian Journal of Fisheries, 2011)
Investigations on the food and feeding habits were carried out on theHimalayan mahseer with a view to provide information on how the habits ofthe fish differ in different tributaries of the Ganga river system. Highestpercentage of insect larvae and n3rmphs was found in the stock of Nayar (72.1-89.8 %) and Saung (76.0-92.0 %). In the Ganga, animal matter accounted for40-100 %, while in the migratory stock of the Alaknanda it was 76.0-88.07 %.Fish remains were more common in the Ganga stock (2.85-60 %), least in theSaung (0.1-0.8 %) and none in mahseer from Alaknanada and the Nayar. Plantmatter (diatoms, green algae and macrophytes) ranged from 0-60 ; 6-20 ; 6.22-19.3 and 4-8 % in the river Ganga, Saung, Nayar and Alaknanda respectively.Organic debris contributed 6.3 ± 0.71, 3.6 ± 0.0 and 36.0 ± 0.2 % of the dietsin the Alaknanda, Ganga, Nayar and Saung respectively. On the basis of thepercentage composition of food the fingerlings exhibited a greater degree ofomnivorous tendency. However, RLG values (0.42-21.11) indicated theircarnivorous tendency. The juveniles and sexually immature individuals werefound to be carnivorous. The tendency of omnivorous diet persists in higherage groups (6+). The RLG values increased with increasing length of the fishindicating suitability of gut for omnivorous diet.